APPLICATION OF GREEN COMPOST FOR THE IMPROVEMENT OF DRY MATTER YIELD AND CHEMICAL COMPOSITION OF LOLIUM PERENNE (GRASS) - G. Sarwar; H. Schmeisky; M. A. Tahir; Y. Iftikhar; N. U. Sabah (Journal of Animal and Plant Sciences, 2011)
A study was conducted to evaluate the effect of greencompost for improvement of dry matter yield and chemical composition of Lolium perenne grass. For this purpose, three different types of soils i.e. normal cultivated soil, nutrient deficient sandy soil and soil from industrial area dominant in CaSO4 coded as soil A, B and C were used. Greencompost was applied to all soil types (A, B and C) @ 5 and 10 % of soil volume. Greencompost was analyzed for various chemical properties like pH and C: N ratio before adding to the soil. Lolium perennegrass was grown in all the pots those were replicated four times arranged in CRD factorial. After harvesting the grass, plant samples were collected and oven dried at 60 0C. These plant samples were, then analyzed for organic matter, N, Ca, Mg, K and P contents. All data were analyzed statistically. It was observed that organic matter, N percentage and potassium contents in plant samples increased with the application of greencompost. The resultant improvement in chemical composition of plant samples contributed toward significant enhancement in dry matter yield of Lolium perenne grass.
Keywords: Greencompost; Lolium perenne; soil types; organic matter; nitrogen; phosphorus; potassium; calcium and magnesium